Vaccination coverage among school children in Western Greece from 2016 to 2019. Issue 11 (2nd November 2021) - Kanellopoulou, A.; Giannakopoulos, I.; Fouzas, S.; Papachatzi, E.; Nasikas, S.; Papakonstantinopoulou, A.; Dimitriou, G.; Gkentzi, D.
ABSTRACT: Vaccine hesitancy has increased, which has an effect on vaccine uptake. The aim of our study was to investigate childhood vaccination coverage in Western Greece and identify factors affecting it. We also aimed to assess trends in childhood vaccination coverage nationwide. A cross-sectional study was conducted (2016–2019) in all the primary schools in Patras, the third largest city in the country. Data collection was undertaken using child vaccination booklets and questionnaires on socio-demographics. Multiple regression analyses were performed to evaluate relevant associations. We also performed a systematic review of published data on childhood vaccination coverage in Greece during the last two decades. Data for 1657 children was collected and 371 questionnaires were returned. High vaccination coverage (>90%) was observed for the majority of the vaccines. For the pneumococcal conjugate vaccine (PCV), coverage with four doses, as recommended at the time of study, was suboptimal (39.2%). For human papillomavirus vaccines and the meningococcal serogroup B vaccine, full vaccination coverage was 2.6% and 6.5%, respectively. No association with socio-demographics was found for vaccines with high coverage. For PCV the number of doses given was related to Greek nationality (β = 0.185, p < .001) and parental employment status (β = −0.115, p = .043). Compared to previous studies (16 eligible), there was a trend toward higher coverage. Public health interventions should focus on increasing vaccine uptake of specific vaccines among populations with particular characteristics. A national network recording vaccine coverage is urgently required in the country to monitor vaccine uptake and assess trends over time.